THE CONCEPT OF WHISTLEBLOWING: HOW IS IT APPLIED IN MALAYSIA? - Wan Murshida Wan Hashim; Anita Che Hassan; Nor Jaslina Nik Wil; Haslinda Abdul Hamid, (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2025)
Whistleblowing serves as a critical mechanism for promoting transparency and accountability in Malaysia, particularly in the fight against unethical or illegal behaviour such as corruption. This article explores the legal framework surrounding whistleblowing in Malaysia, focusing on the Whistleblower Protection Act 2010. It examines the legal protections afforded to whistleblowers, including laws designed to prevent retaliation and encourage reporting of unethical or illegal behaviours. Additionally, the article explores the role of the enforcement agencies in facilitating and safeguarding whistleblowing activities. This article applied qualitative study by analysing the effectiveness of these legal provisions and institutional support systems. The article offers insights into the effectiveness of the whistleblowing practices in Malaysia. The article concludes with recommendations for strengthening legal protections to better protect those who expose unethical behaviour particularly corruption, emphasizing the need for continued legal reform to ensure whistleblowers can contribute effectively to upholding accountability and transparency in Malaysia.